Effect Of Different Feeding Systems On Growth Performance And Cost Economics In Mecheri Lambs. - Arulnathan , N.; Bandeswaran , C. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was carried out to assess the growth performance and cost economics of different feeding systems, which could be adopted by the farmers for their benefits. The average daily gain was significantly higher (P
Keywords: Mecheri lambs; different feeding system; growth performance; cost economics